Letter to the Editor: Testing game-theoretic comparative statics using Bayesian model selection - Aksoy, O; Weesie, J (Routledge, 2015)
Aksoy and Weesie (2013) propose a formal-game-theoretic model that yields comparative statics predictions about the behavior of actors and actors’ expectations about behaviors of others in nonrepeated Prisoner's Dilemma games. They consider five competing specifications of this model. In this note, we present a Bayesian statistical method to test these five competing specifications, taking the hierarchical nature of the data into account. While this paper is a follow-up to Aksoy and Weesie (2013), the method we discuss is suitable to test multiple comparative statics and is, thus, useful to asses the fit of other game-theoretic models.